Unidades de paisagem e zoneamento: subsídios para o planejamento ambiental na bacia do rio Uberabinha-MG - Rosa, Rafael Mendes (2017)
The improvement of planning and environmental management tools is a necessity that has intensified with the growing demand for natural resources, mainly verified after the second half of the twentieth century. In Brazil, the National Environmental Policy (Law number 6.938, dated August 31, 1981) presents zoning as one of its instruments, which contributes to the strategies for exploitation the natural resources of a certain region, state of the federation or a watershed. The importance of geography in the elaboration of zoning is emphasized by the holistic approach and by the ability to analyze natural and social phenomena at different scales. Thus, the present research presents a proposal of zoning of the Uberabinha river basin, located in the region of the Triângulo Mineiro and Alto Paranaíba, from the notion of landscape in geography. In the analytical stage, bibliographical researches and fieldworks were carried out to diagnose the geological aspects, landforms characteristics, types of soils, drainage network, climatic conditions and the land use and native vegetation cover, as well as procedures in geoprocessing software for the creation thematic maps. In the integration stage, the geological aspects, declivity, soil typologies and the land use and native vegetation cover were selected for determining the action of landscape processes. The application of this methodology resulted in 10 zones, being presented a characterization and general indications for the environmental planning in each of them. Finally, it is expected that the work will be able to subsidize plans, programs and projects focused on the environmental sustainability of the Uberabinha river basin, in addition to contributing to the resumption of methodological discussions about zoning works.